Microbially Induced Calcium Carbonate Precipitation as a Bioremediation Technique for Mining Waste - Samantha M. Wilcox; Catherine N. Mulligan; Carmen Mihaela Neculita (Toxics, 2024)
Mining waste represents a global issue due to its potential of generating acidic or alkaline leachate with high concentrations of metals and metalloids (metal(loid)s). Microbial-induced calcium carbonate precipitation (MICP) is an engineering tool used for remediation. MICP, induced via biological activity, aims to precipitate calcium carbonate (CaCO3) or co-precipitate other metal carbonates (MCO3). MICP is a bio-geochemical remediation method that aims to immobilize or remove metal(loid)s via enzyme, redox, or photosynthetic metabolic pathways. Contaminants are removed directly through immobilization as mineral precipitates (CaCO3 or MCO3), or indirectly (via sorption, complexes, or inclusion into the crystal structure). Further, CaCO3 precipitates deposited on the surface or within the pore spaces of a solid matrix create a clogging effect to reduce contaminant leachate. Experimental research on MICP has shown its promise as a bioremediation technique for mining waste. Additional research is required to evaluate the long-term feasibility and potential by-products of MICP-treated/stabilized waste.